Protease monocomponente obtida a partir de Bacillus licheniformis PWD-1 em dietas com diferentes valorizações nutricionaispara frangos de corte - Carneiro, André Luis Machado (2017)
The objective of this study was to evaluate the effect of adding the protease enzyme 0.05% (Cibenza DP 100) in diets for broilers based on corn and soybean meal with two nutritional matrices. Two experiments were conducted with 5 treatments with a basal corn and soybean meal diet: T1 – basal diet with valued protease matrix twice without the enzyme, T2 – basal diet with valued protease nutritional matrix once without enzyme, T3 – basal diet, T4 – basal diet with valued protease nutritional matrix twice with enzyme and T5 – basal diet with valued protease nutritional matrix once with enzyme. The first experiment was carried out with 1280 chicks Cobb500 strain of 1 to 42 days and the second experiment was carried out with 120 chicks housed in the first experiment, and the chicks were housed in battery cages from 17 to 21 days for digestibility study. The experimental design of the experiments was a randomized block, being in the first experiment the row in the experimental industrial shed the criteria for distribution of the blocks, with 5 treatments and 8 repetitions each containing 32 broilers per box. In the second experiment the floor of the cage was the criteria distribution of the blocks, with 5 treatments and 6 repetitions each containing 4 broilers per cage. The analyzed variables were: digestibility, carcass yield, rest, thighs, wings, abdominal fat and performance variables. In all treatments the data were subjected to analysis of variance, evaluated by the R program, and the means were compared by Tukey test at 10% significance. In the first experiment, it was observed a statistical difference (P <0.10) in the final mean weight, weight gain and feed intake in the pre-initial phase with beneficial results with the enzyme supplementation with valued protease nutritional matrix once. In the period from 1 to 21 days, there was a statistical difference (P <0.10) in feed intake and feed conversion, but with positive results for the control treatment. In the cut yield, there was no statistical difference (P> 0.10) in the most used cuts, similar results between the treatments and the control. Statistically different result (P <0.10) was found with the lowest proportion of abdominal fat in the diet fed with diet supplemented with the enzyme and nutritional matrix valued at one time. In the second experiment, statistical difference (P <0.10) was observed for nitrogen balance, which was positive, resulting in higher retention of nitrogen with lower excretion in the environment. The dry matter retention also showed a statistically different result (P <0.10), with a positive result for the supplementation with the enzyme together with greater metabolizability of the dry matter. Based on this study, the protease enzyme supplementation is recommended along with a valued protease nutritional matrix once, in the pre-initial phase of life of the birds, in order to have a better final weight, better weight gain, lower feed intake, lower proportion of abdominal fat, positive nitrogen balance and higher dry matter retention. Based on this work, it is recommended to supplement the protease enzyme with a valued protease nutritional matrix, especially in the pre-initial phase, in order to have a better final weight, better weight gain, lower feed intake, lower abdominal fat ratio, positive nitrogen balance and higher dry matter retention. In the other stages of life of the birds (initial, growth and final) the enzyme supplementation with a valued protease nutritional matrix was also beneficial, since the results in performance, cut yield and metabolizability were equivalent to control. The treatment diets are reduced in nutritional levels if compared to control diet with ideal dietary level for the broilers, resulting in less expense with the nutrients and maintaining a high yield.